Redesain Kewenangan Dewan Keamanan PBB dalam Statuta Roma sebagai Upaya Penguatan Independensi ICC - Mufti, Muhammad Wildan (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This research examines how the powers of the United Nations Security Council influence the independence of the International Criminal Court and how redesigning these powers can strengthen the integrity of the ICC as an international criminal justice institution. The core problem of the study lies in the tension between the ICC’s universal legal mandate and the Security Council’s referral and deferral mechanisms, which are often shaped by the political interests of major powers. The objective of the research is to analyze the impact of Security Council authority on ICC independence and to formulate a redesign model that is more objective and accountable. The study employs a normative juridical approach by analyzing the Rome Statute, the UN Charter, academic literature, and international legal documents. The findings conclude that reforms to the referral mechanism, deferral authority, and the use of the veto are necessary for the ICC to operate more independently without political pressure at the global level.